The hepatocellular carcinoma risk in patients with HBV-related cirrhosis: a competing risk nomogram based on a 4-year retrospective cohort study - Guo, Dandan; Li, Jianjun; Zhao, Peng; Mei, Tingting; Li, Kang; Zhang, Yonghong (Frontiers in Oncology, 2024)
The study aimed to build and validate competitive risk nomogram predict cumulative incidence of hepatocellular carcinoma (HCC) for patients with hepatitis B virus (HBV)-related cirrhosis.Methods: A total of 1401 HBV-related cirrhosis patients were retrospectively enrolled from January 1, 2011, to December 31, 2014. Application of 20 times imputation dealt with missing data using multiple imputation by chained equations (MICE). The patients were randomly divided into a training set (n=1017) and a validation set (n=384) at a ratio of 3:1. A prediction study was carried out using competing risk model, where the event of interest was HCC and the competing events were death and liver transplantation, and subdistribution hazard ratios (sHRs) with 95% CIs were reported. The multivariate competing risk model was constructed and validated.Results: There was a negligible difference between original database and 20 imputed datasets. At the end of follow-up, the median follow-up time was 69.9 months (interquartile range: 43.8-86.6). The 31.5% (442/1401) patients developed HCC, with a five-year cumulative incidence of 22.9 (95%CI,20.8-25.2%). The univariate and multivariate competing risk regression and construction of the nomogram were performed in 20 imputed training datasets. Age, sex, antiviral therapy history, hepatitis B e antigen, alcohol drinking history and alpha-fetoprotein levels were included in the nomogram. The area under receiver operating characteristic curve (AUC) at 12-, 24-36-, 60-and 96month were 0.68, 0.69, 0.70, 0.68 and 0.80 and the Brier score were 0.30, 0.25, 0.23, 0.21 and 0.20 in validation set. According to cumulative incidence function (CIF), the nomogram effectively screened out high-risk HCC patients from low-risk patients in presence of competing events (Fine-Gray test p < 0.001).The competitive risk nomogram was allowed to be used for predicting HCC risk in individual patients with liver cirrhosis, taking into account both the association between risk factors and HCC and the modifying effect of competition events on this association.